A wine-bracteate new species of Stigmatodon (Bromeliaceae, Tillandsioideae) from Espírito Santo state, Brazil - Manhães, Vitor Da Cunha; Couto, Dayvid R.; Leme, Elton M. C. (Phytotaxa, 2025)
The authors describe and illustrate Stigmatodon vinosus, a hyperepilithic new species living on bare, nearly vertical rock walls of a granitic inselberg from Espírito Santo state, southeastern Brazil, of the Tubo-laciniate stigma type, which is characterized by the prevailingly purple-wine floral bracts and sepals at anthesis. Its well-developed floral bracts, which distinctly exceed the sepals, allows the recognition of the morphological affinity of this new species with S. magnibracteatus, another dweller from Espírito Santo state belonging to the so called Stigmatodon s.str. Other morphological affinities as well as the conservation status of this new species are also discussed.